Mosquito Nest Eradication Behavior to Prevention Dengue Hemorhagic Fever - Saragih, Raymondus; Novitarum, Lilis; Tampubolon, Lindawati F. (Institute Of Computer Science (IOCS), 2024)
Dengue Hemorrhagic Fever (DHF) is a tropical disease that is influenced by the interaction of 3 factors, namely host factors, spreaders, and causes of the disease, prevention of DHF. Prevention of this disease can be done by increasing the behavior of Mosquito Nests Eradication 3M Plus. Community behavior in eradicating DHF disease vectors is very necessary to reduce the prevalence of DHF. This study aims to identify family behavior in mosquito nests eradication activities. This study uses a descriptive design with a population of all patients in the internal medicine room who are hospitalized at Santa Elisabeth Hospital, Medan. The sampling technique used purposive sampling with the inclusion criteria of families who live in the same house and accompany patients during hospitalization at Santa Elisabeth Hospital, Medan in April 2023 as many as 92 people. The instrument used in this study was the mosquito nests eradication behavioral questionnaire. The results showed that respondents who had good behavior were 90.2% of respondents, while 9.8% of respondents showed bad behavior. It is recommended for all patients of Santa Elisabeth Hospital Medan to always implement mosquito nests eradication to prevent DHF.